Evaluación y análisis de algunas reparaciones realizadas en Bogotá D.C. mediante aplicación in-situ de mezclas asfálticas en frio mediante inyección a presión neumática (2017)
"This work consisted in a following up evaluation of 29 road repairs that were made in the year 2015 through the use of a new technology of high-pressure applied cold- mixes. The first part of the document presents the basic concepts of road maintenance, the materials used in these processes and two methodologies that were used to determine the current condition of the segments of the pavements that contain the repairs and to quantify the traffic condition to which they are exposed. These two methodologies were the determination of the Pavement Condition Index (PCI) for each road segment and the quantification of the Equivalent Axle Load Factor for each segment. With the analysis of the results of the two methodologies explained and a visual analysis of the damages presents in the repairs, which was supported by a photographic register, a general analysis was conducted to conclude about the performance of this new technology".-- Tomado del Formato de Documento de Grado.